The Drama of Hunting - Mátyás Szalay (Warszawskie Studia Teologiczne)
In this short essay I demonstrate that the contemporary discussion on animal rights has some problematic presuppositions concerning the role of philosophy. I argue that what is necessary is not so much to resolve the alleged cultural dispute than to re-learn how to approach it contemplatively. A certain type of hunting can offer a highly dramatic and personally transformative encounter with the animal world through which we can consider our participatory relationship with nature. Thus, after a short methodological introduction, I identify the type of hunting that may allow for such an experience. After the dramatic aspect of hunting is described and analyzed, I explain how the encounter with the quarry illuminates man’s paradoxical place in nature and its subordination to humanity. I finish by phenomenologically describing what the gaze of the hunted animal communicates and how witnessing it restores the contemplative context in which an authentic human response might be given to nature.